ANALISA KOMPETENSI WIRAUSAHA DAN STRATEGI DIFERENSIASI PRODUK UNTUK MENINGKATKAN PERFORMA USAHA - Firmansyah, Alif; Maruta, IGN Anom; Novaria, Rachmawati (Jurnal Dinamika Administrasi Bisnis, 2019)
The author conducts research with the title "Entrepreneurship Competency Analysis and Product Differentiation Strategies to Improve Business Performance" to find out how the application of competency standards and product differentiation strategies are applied to improve business performance in SMEs 9996 Kriya Daun Workshop.This study used descriptive qualitative method. Data obtained through observation, interviews and subsequent documentation studies were analyzed using a deductive mindset.The results of the analysis of the 9996 Kriya Daun Workshop Craft has good competence. But there are still things that are less effective such as in terms of organizing and maximizing media for marketing. Product Differentiation Strategy applied has also had a good effect on the performance of the business being run. Evidenced by the ability of MSMEs to penetrate the export market, and business continuity in competing in markets that have been running for 22 years.Keywords: Entrepreneurship Competence, Product Differentiation Strategy and Business Performance